2014
DOI: 10.1111/1462-2920.12423
|View full text |Cite
|
Sign up to set email alerts
|

nifH pyrosequencing reveals the potential for location‐specific soil chemistry to influence N2‐fixing community dynamics

Abstract: A dataset of 87 020 nifH reads and 16 782 unique nifH protein sequences obtained over 2 years from four locations across a gradient of agricultural soil types in Argentina were analysed to provide a detailed and comprehensive picture of the diversity, abundance and responses of the N2 -fixing community in relation to differences in soil chemistry and agricultural practices. Phylogenetic analysis revealed an expected high proportion of Alphaproteobacteria, Betaproteobacteria and Deltaproteobacteria, mainly rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
1
18

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(100 citation statements)
references
References 35 publications
4
75
1
18
Order By: Relevance
“…The dominance of Proteobacteria, especially the Alphaproteobacteria, Betaproteobacteria, and Deltaproteobacteria, would be expected in such soils, as found previously (25). Similarly, NifH cluster I, especially subclusters 1K, 1A, 1J, and 1P, was consistently dominant in all samples as well, a pattern identified in other agricultural soils (34).…”
Section: Discussionsupporting
confidence: 81%
“…The dominance of Proteobacteria, especially the Alphaproteobacteria, Betaproteobacteria, and Deltaproteobacteria, would be expected in such soils, as found previously (25). Similarly, NifH cluster I, especially subclusters 1K, 1A, 1J, and 1P, was consistently dominant in all samples as well, a pattern identified in other agricultural soils (34).…”
Section: Discussionsupporting
confidence: 81%
“…During the past decades, the nifH gene family has been widely analyzed to study diazotrophic microbial communities in various environments, especially in marine and soil ecosystems [5][6][7][8][9][10][11][12][13], resulting in novel insights into the diversity and structure of N 2 -fixing communities. For example, even though Trichodesmium has been found as the major N 2 -fixing cyanobacteria in marine ecosystems [6], a recent study suggested that the contributions of other N 2 fixers are far more significant than previously estimated [14], indicating the important roles of less dominant N 2 fixers.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to that in ocean, it is believed that both symbiotic and free-living diazotrophs contribute significantly to the terrestrial N budget [15]. Although many previous studies focused on the relationship between symbiotic diazotrophs and plants, the diversity and community structure of diazotrophic communities were recently analyzed by several studies [7,8,[11][12][13]16]. It has also been pointed out that the N 2 fixation rates in soil were significantly affected by diazotrophic community structure [11].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, the application and establishment of certain types of vegetation in mine tailings promotes the presence of important free-living nitrogen fixers in these ecosystems Sun, 2011, 2012). And some studies (Huang et al, 2011;Chinnadurai et al, 2014;Collavino et al, 2014) also indicated that NH + 4 -N improved the abundance and diversity of nitrogen-fixing bacteria. Moreover, stimulation of nitrification in the rhizosphere of C. zizanoides was associated with increases in archaeal ammonium monooxygenase (arch-amoA) transcript abundance.…”
Section: Discussionmentioning
confidence: 96%